SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN SISWA YANG LAYAK MENERIMA BANTUAN OPERASIONAL SEKOLAH (BOS) DENGAN METODE WEIGHTED PRODUCT (WP) - Aris Budyanto; Indra Kanedi; Aji Sudarsono (Jurnal Media Infotama, 2023)
Abstract: School operational assistance is a government program which is basically to provide funding for non-operational operating costs for basic education units as the implementers of the compulsory education program. Some of the problems that occur at this time in determining students who are eligible to receive school operational assistance at IT Technology Al-Fath Mukomuko Vocational High School (VHS) are still not effective, the application that is designed and will be implemented is supported by the weighted product method and implemented with flowcharts, Context diagrams, Data Flow Diagrams, Entity Relationship Diagrams, Table Relations and using visual basic net applications and MySQL database as the data base. The researcher's suggestion is that this new application can be used to replace the old system which is still manual at SMK IT Technology Al-Fath Mukomuko.